Potential Application Of Unmanned Aerial Vehicle (Uav) In Fine Scale Seagrass Mapping At Pulau Gazumbo, Penang, Malaysia - Anthonysamy, Shameen Izwan (2021)
Fine scale seagrass usually grows in patches along the intertidal zone which is covered by epiphytes that limits satellite imagery to obtain a clear image. Hence, to overcome this, a drone (DJI Spark) was used to cater high resolution image. This study investigates seagrass distribution with ground data, chlorophyll content and distinguishes seagrass condition. This study also aims to determine application of UAV on mapping and classifying images of fine scale seagrass distribution. Temporal seagrass distribution was analyzed in Pulau Gazumbo. Eight sampling stations consists of 3 quadrants whereby represents upper, middle and lower littoral zones were placed during low peak tide the size of 0.5m × 0.5m. Environmental conditions, shoots and leaves were counted and recorded for further analysis whilst temporal data was retrieved from previous studies (2003, 2006 and 2009). Seagrass leaves were collected for conventional chlorophyll extraction method whereby absorbance was read at 647nm and 664nm. Meanwhile, RS survey comprises drone imagery from each quadrant at 1.5m above ground. GIS analysis was conducted in ENVI 10.4 and ArcMap 10.2 software which includes image processing, Maximum Likelihood classification and mapping. Results showed temporal existence of Halophila ovalis followed by Halophila beccarii and Halophila spinulosa. Statistical assumptions showed insignificant distribution of seagrass between littoral zones and temporal years. Seagrass distribution was higher in the upper (42.5%) and middle littoral zone (43.75%) compared to the lower littoral zone (37.5%) which relates to environmental measures.